2017
DOI: 10.1186/s12863-017-0569-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification and integrated analysis of differentially expressed lncRNAs and circRNAs reveal the potential ceRNA networks during PDLSC osteogenic differentiation

Abstract: BackgroundResearchers have been exploring the molecular mechanisms underlying the control of periodontal ligament stem cell (PDLSC) osteogenic differentiation. Recently, long noncoding RNAs (lncRNAs) and circular RNAs (circRNAs) were shown to function as competitive endogenous RNAs (ceRNAs) to regulate the effect of microRNAs (miRNAs) on their target genes during cell differentiation. However, comprehensive identification and integrated analysis of lncRNAs and circRNAs acting as ceRNAs during PDLSC osteogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
155
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 145 publications
(155 citation statements)
references
References 51 publications
0
155
0
Order By: Relevance
“…LncRNA H19 also functioned as ceRNA of miR‐141 and miR‐22, both of which were negative regulators of osteogenesis . Through bioinformatics analysis, Gu et al identified 147 lncRNAs totally that were predicted to interact with miRNAs and compete for miRNA binding sites with mRNAs in osteogenic differentiation of periodontal ligament stem cells, revealing the potential lncRNA ceRNA networks . In hADSCs osteogenic differentiation, the differentially expressed lncRNAs were also identified, and lncRNA H19 was found to significantly influence the expression of osteogenesis‐related genes ALPL and Runx2 .…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA H19 also functioned as ceRNA of miR‐141 and miR‐22, both of which were negative regulators of osteogenesis . Through bioinformatics analysis, Gu et al identified 147 lncRNAs totally that were predicted to interact with miRNAs and compete for miRNA binding sites with mRNAs in osteogenic differentiation of periodontal ligament stem cells, revealing the potential lncRNA ceRNA networks . In hADSCs osteogenic differentiation, the differentially expressed lncRNAs were also identified, and lncRNA H19 was found to significantly influence the expression of osteogenesis‐related genes ALPL and Runx2 .…”
Section: Discussionmentioning
confidence: 99%
“…It was predicted that circRNAs would combine with miRNA and compete for the binding sites on the miRNA with mRNAs . CircRNAs expression would alter the mRNA expression by targeting miRNAs that were binding to the mRNAs chosen.…”
Section: Introductionmentioning
confidence: 99%
“…If they are located in the nucleus, they are mainly involved in the process of transcription and chromatin remodelling; when they are located in the cytoplasm, they principally participate in post-transcriptional gene regulation by forming complexes with specific proteins or acting as ceRNAs [41,42]. Since ceRNAs are important regulators between lncRNAs and microRNAs [43][44][45][46][47], we focused on the ceRNA mechanism of 150Rik and miR-451 in this study. We found that miR-451 is directly targeted by lncRNA 150Rik and IGF1R is the target gene of miR-451.…”
Section: Discussionmentioning
confidence: 99%